Effect of Multiple Hole Distribution and Shape Based on Particle Flow on Rocklike Failure Characteristics and Mechanical Behavior - Zhiguo Xia; Ning Jiang; Huisan Yang; Liu Han; Haiyang Pan; Zhenhua Zhao; Quanlin Feng (Advances in Civil Engineering)
Based on the particle flow code, numerical models of vertical and horizontal orientations of holes with different shapes were established, and the effects of preexisting holes with different shapes and arrangement patterns on the mechanical behaviors and failure characteristics of rocklike materials were studied. The evolution trend of the stress field is discussed by taking a circular hole as an example. The results show that the existence of holes reduces the peak stress, peak strain, and elastic modulus of the sample, and different shapes of holes and different arrangement patterns have different effects on the mechanical properties and damage degree of the sample and significantly affect the horizontal orientation model. Before crack formation, the compressive stress and tensile stress concentration areas of each sample are located at the left and right ends and the upper and lower ends of the hole, respectively. After model failure, the compressive stress and tensile stress concentration areas of each sample are relatively scattered. In the vertical orientation model, the middle area of vertical holes is the main compressive stress concentration area, which is approximately “columnar” distribution. In the horizontal orientation model, the compressive stress concentration area between the holes is cross distribution and approximately “X” type distribution. The vertical orientation model sample forms a “columnar” distribution to bear the applied load with a more favorable bearing orientation.